Pengaruh Pemberian Monosodium Glutamat Terhadap Jumlah Sel Purkinje Cerebellum Pada Tikus - Ilham Nugroho (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Monosodium glutamate is a sodium salt of glutamic acid which is one of the most common amino acids found in nature. Although monosodium glutamate has the ability to increase appetite, a case has been reported that monosodium glutamate can be toxic to humans and experimental animals. The cerebellum cortex contains purkinje cells and a layer of granular cells. Excessive accumulation of glutamate in purkinje cell synapses in the cerebellum cortex can cause a decrease in the neuronal ability to maintain normal levels of glutamate resulting in death of purkinje cells and impaired synaptic function. Objective: To determine the effect of monosodium glutamate administration on the number of cerebellar purkinje cells of rats. Methods: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results: Administration of monosodium glutamate to rats at a dose of 3.5 mg/g bw per day for 10 days with parenteral administration resulted in a decrease in the number of purkinje cells in the rat's cerebellum. Conclusion: Excessive accumulation of monosodium glutamate with glutamate as the main component causes a decrease in the number of of cerebellar purkinje cells of rats.